Implementation of patient-reported outcome measures and patient-reported experience measures in melanoma clinical quality registries: a systematic review. Issue 2 (11th February 2021) - Blood, Zachary; Tran, Anh; Caleo, Lauren; Saw, Robyn; Dieng, Mbathio; Shackleton, Mark; Soyer, H Peter; Arnold, Chris; Mann, Graham J; Morton, Rachael L
Abstract : Objectives: To identify patient-reported outcome measures (PROMs) and patient-reported experience measures (PREMs) in clinical quality registries, for people with cutaneous melanoma, to inform a new Australian Melanoma Clinical Outcomes Registry; and describe opportunities and challenges of routine PROM/PREM collection, especially in primary care. Design: Systematic review. Primary and secondary outcome measures: Which PROMs and PREMs are used in clinical quality registries for people with cutaneous melanoma, how they are collected, frequency of collection, participant recruitment methods and funding models for each registry. Results: 1134 studies were identified from MEDLINE, PreMEDLINE, Embase, PsychInfo, Cochrane Database of Abstracts of Reviews of Effects databases and TUFTS Cost-Effectiveness Analysis Registry, alongside grey literature, from database inception to 5th February 2020. Following screening, 14 studies were included, identifying four relevant registries: Dutch Melanoma Registry, Adelphi Real-World Disease-Specific Programme (Melanoma), Patient-Reported Outcomes Following Initial treatment and Long-term Evaluation of Survivorship Registry, and Cancer Experience Registry. These used seven PROMs: EuroQol-5 Dimensions, Functional Assessment of Cancer-General (FACT-G) and FACT-Melanoma (FACT-M), European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire-Cancer 30 (EORTC QLQ-C30), Fatigue Assessment Scale Hospital Anxiety and Depression Scale, Patient-Reported Outcome Measures Information System-29 and one PREM; EORTC QLQ-Information Module 26. PROMs/PREMs in registries were reported to improve transparency of care; facilitate clinical auditing for quality assessment; enable cost-effectiveness analyses and create large-scale research platforms. Challenges included resource burden for data entry and potential collection bias toward younger, more affluent respondents. Feedback from patients with melanoma highlighted the relevance of PROMs/PREMs in assessing patient outcomes and patient experiences. Conclusions: Clinical registries indicate PROMs/PREMs for melanoma care can be incorporated and address important gaps, however cost and collection bias may limit generalisability. PROSPERO registration number: CRD42018086737.